IMPROVING STUDENTS’ SPEAKING SKILLS THROUGH INTERVIEW TECHNIQUE - Sianipar, Tria Romauli; ., Regina; Supardi, Iwan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: The purpose of this research is to improve students’ speaking skills by using interview technique. This research used a classroom action research as form of research. The subject of this research is class VIII A at SMP Negeri 19 Pontianak in academic year 2014/2015 which consists of 40 students. The techniques of collecting data in this research are observation and measurement and the tools of collecting data are observation checklist, field notes and test of speaking. Based on the data revealed in observation, there were improvements in students’ speaking skills in every cycle. Students’ mean score in the first cycle was 48% which was categorized poor. In the second cycle the mean score of students was 59% which was categorized poor to average. Then, in the third cycle the mean score of students was 72% which was categorized average to good. In conclusion, Interview Technique improves the students’ speaking skills at second grade students of SMP Negeri 19 Pontianak in academic year 2014/2015. Keywords: Speaking skills, Interview technique Abstrak: Penelitian ini bertujuan untuk meningkatkan kemampuan berbicara siswa dengan menggunakan teknik Interview. Metode dalam penelitian ini adalah penelitian tindakan kelas dengan subjek penelitian siswa kelas VIII A SMP Negeri 19 Pontianak tahun ajaran 2014/2015 yang berjumlah 40 siswa. Teknik pengumpulan data yang di gunakan adalah observasi dan pengukuran dengan alat pengumpulan data daftar observasi, catatan lapangan dan uji kemampuan berbicara. Data yang diperoleh melalui pengamatan mengungkapkan bahwa kemampuan berbicara siswa meningkat disetiap siklus. Nilai rata-rata siswa pada siklus pertama adalah 48% yang dikategorikan sangat rendah. Pada siklus kedua, nilai rata-rata siswa adalah 59% yang dikategorikan rendah. Kemudian, pada siklus ketiga, nilai rata-rata siswa adalah 72% yang dikategorikan baik. Kesimpulannya, teknik Interview meningkatkan kemampuan berbicarasiswa kelas dua SMP Negeri 19 Pontianak pada tahun ajaran 2014/2015. Kata kunci: Kemampuan berbicara, teknik Interview